Effect of preprandial exercise on the basal and postprandial intermediary metabolism in patients with type 2 diabetes at sea level - Garmendia, Fausto (2019)
Introduction. The therapeutic support of the metabolic control of diabetes mellitus type 2 (DM2) are the diet and physical activity.Objetive: To study the effect of a short and casual exercise on the basal and postprandial intermediary metabolism of individuals with DM2. Methods. A total of 16 female and 15 male, DM2 patients, 40 to 68 years old, were included in a experimental, tranversal study. They were submitted to a basal (A) and post-exercise (B) tests, the last one consisting in 30 minutes walking at 4 Km/hour on a treadmill, Under fasting, state, glucose, total cholesterol , HDL cholesterol, triglycerides, insulin and non-sterified fatty acids (NEFA) were measured in blood. Cholesterol VLDL, LDL, Non-HDL and HOMA were calculated. After a breakfast consisting in 55,5% fat, 37,2 % carbohydrates, 7,34% proteins containing 730 Kcal, glucose, insulin, triglycerides and NEFA were measured during 6 hours. Results: The exercise produced a lowering of glucose, insulin and NEFA during postprandial state. Conclusion: The exercise ameliorates the metabolic control at postprandial state of DM2.